2022
DOI: 10.3389/fgene.2022.873641
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Phenotype of Uncommon Charcot–Marie–Tooth Genotypes Complicated With Inflammation Evaluated by Genetics and Magnetic Resonance Neurography

Abstract: The pathogenesis of Charcot–Marie–Tooth (CMT) disease, an inherited peripheral neuropathy, is associated with more than 60 nuclear genes. We reported a rare phenotype of the uncommon CMT genotype complicated with neuroinflammation, that is, an MPZ mutation, NC_000001.11 (NM_000530.6): c.308G > C detected by next-generation sequencing. Moreover, we present a case of the CMT type 1B, with atypical presentation as two patterns of hypertrophy in the brachial and lumbosacral plexus, as well as enhancement in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…In particular, it has been suggested that the manifestations and the course of the disease in some patients are modified by a superimposed autoimmune/inflammatory response, possibly driven by the changed immunogenicity of an abnormal MPZ protein, in keeping with the experimental observations of secondary autoimmunity and CIDP-like manifestations in P0 knockout mice [41,42]. In some patients, consistent features of an acute/subacute onset [20], rapidly progressive [43] or stepwise-fluctuating course [19,44,45], elevation of cerebrospinal fluid protein [19,20,22,[44][45][46], and response to immunotherapies [22,[44][45][46] were described, including cases with painful neuropathy. Other comorbidities potentially influencing the neuropathy expression, such as diabetes or B12 deficiency that are often associated with painful neuropathy, are not mentioned in the case studies.…”
Section: Discussionmentioning
confidence: 73%
“…In particular, it has been suggested that the manifestations and the course of the disease in some patients are modified by a superimposed autoimmune/inflammatory response, possibly driven by the changed immunogenicity of an abnormal MPZ protein, in keeping with the experimental observations of secondary autoimmunity and CIDP-like manifestations in P0 knockout mice [41,42]. In some patients, consistent features of an acute/subacute onset [20], rapidly progressive [43] or stepwise-fluctuating course [19,44,45], elevation of cerebrospinal fluid protein [19,20,22,[44][45][46], and response to immunotherapies [22,[44][45][46] were described, including cases with painful neuropathy. Other comorbidities potentially influencing the neuropathy expression, such as diabetes or B12 deficiency that are often associated with painful neuropathy, are not mentioned in the case studies.…”
Section: Discussionmentioning
confidence: 73%